Neutrosophic Soft Tri-Topological Spaces - Dadas, Hasan; Demiralp, Sibel (ASPG Publishing LLC, 2021)
In this study, the concept of neutrosophic soft tri-topological space is defined as a generalization of neutrosophic soft bitopological space. Then neutrosophic soft tri-open and tri-closed sets are defined and in this space. Also, some basic properties of these new types of open and closed sets are investigated and supported by many examples to further clarify the study.
Keywords: Neutrosophic set; Neutrosophic soft set; Soft bitopological space; Neutrosophic soft bitopological space; Neutrosophic soft tri-topological space.